Approximate analytic solutions of the modified Kawahara equation with homotopy analysis method - Kurulay, Muhammet (SPRINGEROPEN, 2012)
In this paper, we applied the homotopy analysis method (HAM) to solve the modified Kawahara equation. Numerical results demonstrate that the methods provide efficient approaches to solving the modified Kawahara equation. It is shown that the method, with the help of symbolic computation, is very effective and powerful for discrete nonlinear evolution equations in mathematical physics.
Keywords: the modified Kawahara equation; homotopy analysis method; PERTURBATION METHOD; DIFFERENTIAL-EQUATIONS; SMALL PARAMETERS; Mathematics